Ethnic Differences in Presentation and Severity of Alcoholic Liver Disease - Levy, Robert (Alcohol Clin Exp Res, 2015)
BACKGROUND: The frequency of alcoholic liver disease (ALD), including alcoholic steatosis, hepatitis and cirrhosis, varies significantly by ethnicity. METHODS: With the goal to assess the role of ethnicity in determining the age of onset and severity of ALD and to compare the risk factors for its progression among ethnic groups, we conducted a retrospective chart review of all patients with ALD who were admitted or were followed as outpatients at University of California Davis Medical Center between 2002 and 2010. After excluding HBsAg and HIV positive subjects, we reviewed the charts of 791 ALD patients including 130 with alcoholic fatty liver, 154 with alcoholic hepatitis, and 507 with alcoholic cirrhosis. RESULTS: When controlling for all variables in the model, Hispanic patients presented at significantly 4-10 years younger ages than White/Caucasian patients, in each of the three disease severity categories and the results were confirmed after excluding HCV Ab/RNA positive subjects. There were more obese Hispanic patients than White/Caucasian patients, whereas the proportion of patients with hepatitis C was significantly greater in African/American subjects with alcoholic hepatitis and the proportion of patients with diabetes mellitus was significantly lower in White/Caucasian subjects than in Hispanic subjects with cirrhosis. The proportion of subjects with severe alcoholic hepatitis was similar in Hispanic and White/Caucasian patients, but lower in African/American subjects. CONCLUSION: Ethnicity is a major factor affecting the age and severity of presentation of different subtypes of ALD.